Effect of Pregabalin on Erectile Function and Penile NOS Expression in Rats with Streptozotocin-Induced Diabetes - Amany, S.; Heba, K. (Experimental and Clinical Endocrinology & Diabetes, 2013)
To investigate the effect of pregabalin on erectile function and on the penile expression of nitric oxide synthase (NOS) isoforms in diabetic rat models.Male Sprague-Dawley rats were injected with streptozotocin to induce diabetes mellitus. The rats with blood glucose levels above 300 mg/dL were selected for the study. Those were randomly divided into 2 groups (N=10 per group): i) EDDM (erectile dysfunction diabetes mellitus )group fed with saline and ii) EDDM+Pregabalin treated group receiving pregabalin (10 mg/k/day) by intragastric administration. 10 animals served as a control group and received no streptozotocin. 4 weeks later, the erectile function of the rats was assessed by recording frequency of erection after subcutaneous apomorphine (80 ug/kg) injection. Superoxide anion generation and the expression of mRNA of nNOS and eNOS were evaluated in corpora cavernosum tissue.Penile erection, the expression of both nNOS, eNOS and superoxide generation were significantly decreased in pregabalin treated group compared to control group.Treatment with pregabalin for 4 weeks decreases superoxide production but cannot improve erectile dysfunction in diabetic rats probably by inhibiting Ca2 +  channel-mediated NOS activation.
Keywords: diabetes; erectile dysfunction; nitric oxide synthase; pregabalin